Formulation and Evaluation of Phenytoin Sodium Buccoadhesive Polymeric Film for Oral Wounds: Phenytoin sodium buccoadhesive polymeric film - Rahim Bahri Najafi; Zahra Rezaei; Omar Najm (Iranian Journal of Pharmaceutical Sciences, 2011)
In recent decades, most of researchers in pharmaceutical preparations have focused increasingly on new formulations that control the site and amount of drug delivery. Mucoadhesive dosage forms are available for systemic or local treatment. The mucoadhesive dosage forms are introduced in various forms such as tablets, gels, ointments, patches and polymeric films. For buccal wound and injury the polymeric films may be preferred due to flexibility, comfort, longer residence time, protection of the wound surface and promotion of the wound healing. Most of dentists apply phenytoin sodium suspension as a gargle for promoting healing in dental surgery. In this study, a novel phenytoin sodium mucoadhesive film consisting of two layers of polymeric film was prepared by solvent casting method. One layer contained various ratios of carbapol 934, NaCMC, HPMC and a constant proportion of PEG 400 as plasticizer. The other layer contained cellulose acetate phethalate which acts as water resistant for unidirectional release. The film’s mechanical properties such as swelling, in vitro adhesion/drug release and residence time by using human volunteers were measured.among different polymers the HPMC/Na CMC/CP 934 were selected and thirteen formulations (F1-F13) were prepared. The best formulation in physical properties were F1, F6, F8, F9 and F13. F8 had the highest and F1 had the lowest swelling index, and all formulations had high adhesive strength. Formulation F6 had a fast release pattern during the first 30 mins, but F8 had the highest amount of release in 3 hours. F1 had the lowest amount of release during 3 hours. F1 had the longest residence time while F8 and F9 showed the shortest residence time accompanied with detachment. From the current study, one can conclude that the buccoudhesive film of F13 containing 60% HPMC, 20% NaCMC and 20% CP had zero order models of drug release and possesses suitable swelling profile, good adhesion strength, appropriate residence time and produced no irritation. Optimum ratio for the mucoadhesive polymeric film composed of Carbopol/Na CMC/HPMC, was 20/30/40 (wt/wt/wt) in terms of flexibility, comfort, long residence time, swelling, and bioadhesive force.